ANALYSIS OF AGRICULTURAL LAND RENTAL PATTERNS IN KALIWEDI DISTRICT ACCORDING TO ISLAMIC PERSPECTIVE - Qothrunnada, Rofidah; Busthomi, Achmad Otong; Samsudin, Samsudin (Islamic Economic and Business Journal, 2025)
This study aims to analyze the pattern of agricultural land rental that occurs in the community and examine its suitability with the principles of the ijarah contract from an Islamic perspective. The research method used is descriptive qualitative with a field study approach (Field Research). Data were obtained through observation, documentation and in-depth interviews with farmers or land tenants. Based on the results of the study, it can be concluded that the system used by land tenants is to use an annual rental pattern system, a seasonal intercropping system with the main commodity being rice. In practice, it generally uses verbal agreements based on trust. Among the villages studied, there are differences in price due to factors such as soil fertility quality and irrigation access. There are several factors that influence land rental, namely land conditions and water availability, social relations between owners and tenants and religious factors. Viewed from an Islamic perspective, this agricultural land rental pattern can generally be justified as long as it meets the pillars and requirements of the ijarah contract, such as clarity of the lease object, the contract is carried out with the consent of both parties, and the practice takes place in the context of mutual assistance and mutual respect for each other. However, there needs to be an increase in public understanding about the importance of transparency and clarity of rental contracts in order to avoid practices that lead to gharar (unclarity) and potential disputes in the future.